RECONFIGURING FAMILY COMMUNICATION IN THE DIGITAL AGE: TOWARD A VALUE NEGOTIATION MODEL AMONG URBAN MUSLIM FAMILIES - Mohammad Ismed; Ummy Hanifah (Politeknik Negeri Media Kreatif, 2026)
This research explores the transformation of family communication in the digital era, focusing on value negotiations within urban Muslim families. The rise of digital platforms has altered patterns of interaction, leading to conflicts between digital culture and Islamic values in increasingly interconnected societies like Indonesia. Although previous studies have looked into the influence of digital media on familial relationships, there has been little emphasis on how religious values shape communication practices. Employing an interpretive phenomenological methodology, this study examines five urban Muslim families through comprehensive interviews, observations, and documentation. The data were analyzed using the Miles and Huberman interactive model. The findings identify five unique communication models: adaptive-dialogical, relational-situational, restrictive-normative, individual self-regulated, and hybrid-negotiative. Value negotiation is recognized as an essential process that enables families to harmonize religious values with digital interactions. This study introduces a model of digital family communication based on value negotiation, which enhances theoretical understanding and practical application in the context of platform-driven environments